ASSESSING TEACHERS’ PERCEPTION ON THE EFFICIENCY (SUCCESS) OF INDUCTIVE APPROACH IN AN ESL/EFL CLASSROOM: GRAMMAR IN CONTEXT - Taj Mohammad; Soada Idris Khan (English Review: Journal of English Education, 2017)
The present research attempts to assess teachers' perception on the success of using inductive approach in the classroom at Preparatory Year Program, Najran University. It also inquires the difficulties that are usually faced by students (in teachers' opinion) in a grammar class. In order to collect data, 20 teachers were requested to fill in a questionnaire consisting of ten statements (based on key elements of inductive teaching). The questionnaires were analyzed by using 5-Point Likert-scales of agreement. Besides, the researcher also personally interviewed the teachers by using a set of certain questions covering the same theme. The study is divided into two parts; the first part contains detailed analysis and discussion on the statements of the questionnaire and the second part comprises a detailed analysis and discussion on the responses of interview. As results, it is revealed that a majority of teachers supported the use of inductive approach in the classroom because of its learner-centred nature. Inductive methods help students acquire the critical thinking and self-directed learning skills (Prince Felder, 2007).  However, some teachers (with a negligible percentage) were not so enthusiastic about using inductive approach. Keywords: teachers' perceptions, descriptive and prescriptive grammar, inductive approach